Pelatihan Penulisan Karya Ilmiah Berstandar Internasional Berbasis Teknologi Kecerdasan Buatan bagi Akademisi - Nur Aeni; Baso Jabu; Amirullah Abduh; Mansyur Mansyur (Jurnal Abdimas Indonesia, 2025)
This community service activity was driven by the low quality of scientific writing among teachers and students, which is caused by limited mastery of academic writing techniques and the underutilization of artificial intelligence (AI) technologies. Objective: This program aimed to enhance the academic writing skills of teachers, staff, and students of SMAN 3 Selayar through training that integrates AI-based tools such as Jenni AI, QuillBot, and ChatGPT. Method: The program was carried out over eight training sessions spanning two months, consisting of workshops, hands-on practice, and intensive mentoring. The effectiveness of the training was evaluated using pre-tests and post-tests, analyzed quantitatively through statistical tests. Results: The result showed significant improvements in participants' writing skills, particularly in language accuracy and paragraph structure. The use of AI applications proved effective in correcting grammar, organizing paragraphs systematically, and improving cohesion and coherence. Conclusion: AI-assisted training proved effective in improving the quality of academic writing and boosting participants’ confidence in publishing articles in reputable journals. These findings highlight the importance of integrating technology into academic capacity-building programs and suggest further research on the long-term impact of AI on scientific writing quality.